Testing Accuracy and Fluency in Speaking Through Communicative Activities - Fanny Stella Torres Vigoya (Asociación Colombiana de Profesores de Ingles, 2016)
For many years, all those interested in the teaching of English as a foreign language have analysed, investigated and discussed the role and importance of speaking skills and the way they could be tested in the teaching-learning process. It has been noted that the way oral production is being tested is definitely important in order to obtain better results in the effective and appropriate use of spoken language. This essay deals with some topic-linked ideas for teachers to test oral accuracy and fluency in a well organised and systematic way by using meaningful, interesting and motivating activities.